Sistem Informasi Administrasi dengan Fitur Data Mining Market Basket Analysis pada UD.Asia Stationery - Ricky Djunaidy; Gregorius Satia Budhi; Alexander Setiawan; Djoni Haryadi Setiabudi (Jurnal Infra, 2017)
Asia Stationery stores located in Banjarmasin, is a store that sells items such as stationery, office equipment, and others. Business processes performed by these stores are ordering and purchasing goods from suppliers and selling goods to the customer. The store has a sales package (combined goods), the combined variations of selected items for sale by the owner of a little shop and not much choice for customers when making a purchase to the store. The store owner also difficulties when they want to add things they do not understand a combined package of goods suitable in situations stores certain months. The whole process of business done by the stores still rely on manual control so that the possibility of human error is very large. Based on the existing situation required the completion of the method by using Data Mining association rules and administrative information systems based website for the store to be computerized and improve the control of business processes in the store.Based on the existing situation, namely the completion of the necessary administrative information systems based website for the store to be computerized and improve the control of business processes in the store. This application is built using the programming language CSS, AJAX, MySQL, JSON, Javascript, HTML, PHP, and MySQL Bootstrap as a storage medium (database). The end result of making this application is that it can make the process of purchasing, registration stock card, sales, and process of data mining market basket analysis methods are integrated with the database. Additional features to support existing data as a reminder of stock items, income, cost of goods sold average method, on the placement of goods, inventory recommendations are also included.